Cost-benefit analysis of choosing green construction materials: a case study approach from India. (2nd October 2021) - Sudarsan, J.S.; Sridharan, Srividhya Raju
Building and construction industry contributes more than 35% of global greenhouse gas (GHG) emission, making it one of the major contributors towards global warming. To ascertain the embodied carbon emitted at the different phases of constructing a structure, a trial study was carried out by observing two buildings - a residential building in the city of Bengaluru and a commercial building in the city of Hyderabad, India. This assessment was carried out using standard empirical formula used for estimating the carbon emission of construction building materials. Based on the estimation it was inferred that usage of sustainable material such as recycled steel and ferrock can bring down emissions by around 87%. The total emission and associated cost by adopting sustainable building materials is also estimated and compared with that of conventional material. The study justifies the increased cost of sustainable material through a Cost-Benefit Analysis approach.